A conceptualisation of relationship quality in construction procurement. Issue 6 (August 2016) - Jelodar, Mostafa Babaeian; Yiu, Tak Wing; Wilkinson, Suzanne
Abstract: Relational contracting is often regarded as means to improve performance and profit margins in managing projects. A continuum of contracts in construction projects attempts to provide fit for purpose relationships to different working conditions; hosting levels of relationship quality. This study aims to explore contracting methodologies within construction procurement in search of practical and manageable relationship quality attributes. Initially relational attributes such as teamwork, commitment and trust along with seven main strategies for achieving these attributes are extracted from relevant studies. In the second stage construction expert interviews suggest that performance satisfaction is also a practical attribute and necessity of relationship quality. The study proposes a framework of actions and seven strategies which can facilitate the attributes associated with relationship quality. Finally based on the framework and three case studies five levels of transaction, action, strategy, attribute and relationship are demonstrated for relationship quality evaluation in construction project's procurement practices. Highlights: Trust, commitment, and teamwork and performance satisfaction are identified relationship quality attributes in construction A framework of actions, strategies and attributes are proposed for relationship quality Five levels of transaction, action, strategy, attribute and relationship is suggested for relationship quality status